The Impact of Diversity and Inclusion Policies and Anti-Discrimination Training on Employee Commitment and Productivity in Multinational Companies in Central Java - Rendi Mark Sowaha Duha; Thitus Gilaa (North Press, 2024)
This study examines the impact of diversity and inclusion (D&I) policies and anti-discrimination training on employee commitment and productivity in multinational companies located in Central Java. Using a quantitative approach, data were collected from 120 employees through a structured questionnaire, with responses measured on a 5-point Likert scale. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed to analyze the relationships between the variables. The findings indicate that both D&I policies and anti-discrimination training have significant positive effects on employee commitment and productivity. The results suggest that fostering an inclusive and supportive workplace through effective policies and training programs enhances employee loyalty, motivation, and job performance, ultimately benefiting the organization. These insights offer practical recommendations for human resource management in multinational companies seeking to optimize their workforce management strategies.